Incorporação de resíduo de perfuração em matriz cerâmica: estabilização por solidificação - Câmara, Ana Paula Costa (2013)
One of the waste generated during the drilling of oil wells are gravel which are impregnated of drilling fluid. This residue consists of highly toxic chemicals, including toxic metals. This study suggests an alternative process to the treatment of this waste, by incorporating it the form of raw material in the ceramic matrix , and by solidification and stabilize the metals present, Aluminum (Al), Iron (Fe), Manganese (Mn) and Zinc (Zn). The raw materials were characterized by the techniques of X ray fluorescence (FRX), X ray diffraction (DRX), laser granulometry (GL), thermogravimetry (TG) and differential thermal analysis (ADT). To evaluate the percentage of gravel effect the environmental and technological properties were obtained from formulations containing 0, 10 and 20 % by weight of gravel in the ceramic matrix. After sintering at temperatures 1080, 1120 and 1160 °C, the samples were tested for water absorption, the linear shrinkage firing, voltage of rupture and solubility. The results obtained showed that the stabilization by solidification, is a viable alternative to safe disposal of waste drilling. Ceramics products can be used in the manufacture of solid bricks